2002
DOI: 10.1038/sj.jp.7210672
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a New Low-flow Sidestream Capnography Technology in Newborns: A Pilot Study

Abstract: Low-flow capnography with Microstream technology accurately measured alveolar CO(2) in newborns without pulmonary disease, as demonstrated by normal PetCO(2)-PaCO(2) gradients. The measured PetCO(2)-PaCO(2) gradient, as expected, was significantly higher in newborns with pulmonary disease. We also identified four quantitative waveform parameters that may be useful in differentiating between mechanically ventilated newborn patients with and without lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 25 publications
3
45
1
Order By: Relevance
“…Due to the strong correlation between P a − et CO 2 and alveolar dead space, these authors state that from a clinical perspective, measuring P a − et CO 2 to monitor NO inhalation therapy is simpler than measuring alveolar dead space as an ordinary end-tidal CO 2 monitor can substitute for a sophisticated system of dead space measurements requiring simultaneous measurements of CO 2 elimination and tidal volume. Hagerty et al (2002) found a higher P a − et CO 2 gradient when comparing newborns with pulmonary disease and those who received mechanical ventilation for non-pulmonary conditions. However, McDonald et al (2002) showed in a large study in 129 ventilated infants using 2,184 arterial blood and gas samples that in most of the patients, P a − et CO 2 is small enough such that P et CO 2 monitoring enables the clinician to adequately monitor ventilation and gas exchange.…”
Section: The P a − Et Co 2 Differencementioning
confidence: 94%
See 1 more Smart Citation
“…Due to the strong correlation between P a − et CO 2 and alveolar dead space, these authors state that from a clinical perspective, measuring P a − et CO 2 to monitor NO inhalation therapy is simpler than measuring alveolar dead space as an ordinary end-tidal CO 2 monitor can substitute for a sophisticated system of dead space measurements requiring simultaneous measurements of CO 2 elimination and tidal volume. Hagerty et al (2002) found a higher P a − et CO 2 gradient when comparing newborns with pulmonary disease and those who received mechanical ventilation for non-pulmonary conditions. However, McDonald et al (2002) showed in a large study in 129 ventilated infants using 2,184 arterial blood and gas samples that in most of the patients, P a − et CO 2 is small enough such that P et CO 2 monitoring enables the clinician to adequately monitor ventilation and gas exchange.…”
Section: The P a − Et Co 2 Differencementioning
confidence: 94%
“…In neonates with a minute ventilation of about 200 mL/min/kg body weight, the suction flow must be sufficiently low to prevent dilution by surrounding air that will occur when the expiratory gas flow rate falls below the suction flow rate. A microstream capnograph using a suction flow of 30 mL/min and a miniaturized sample chamber has been developed, thus, improving the measurement accuracy for intubated infants (Hagerty et al 2002;Kugelman et al 2008).…”
Section: Educational Aimsmentioning
confidence: 99%
“…3,4,21,22 Clinically, the Paco 2 -Petco 2 gradient can be used to document and monitor a variety of respiratory or cardiac conditions. [24][25][26][27][28] For example, neonatal infants with pulmonary disorders such as persistent pulmonary hypertension, respiratory distress syndrome, pneumonia, or meconium aspiration had a significantly higher Paco 2 -Petco 2 gradient (7.4 ± 3.3 mm Hg) when compared with aged-matched healthy controls (3.0 ± 2.4 mm Hg). 25 The Paco 2 -Petco 2 gradient has also been used to support the diagnosis of pulmonary thromboembolism as well as to monitor efficacy of thrombolysis in patients with pulmonary thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] For example, neonatal infants with pulmonary disorders such as persistent pulmonary hypertension, respiratory distress syndrome, pneumonia, or meconium aspiration had a significantly higher Paco 2 -Petco 2 gradient (7.4 ± 3.3 mm Hg) when compared with aged-matched healthy controls (3.0 ± 2.4 mm Hg). 25 The Paco 2 -Petco 2 gradient has also been used to support the diagnosis of pulmonary thromboembolism as well as to monitor efficacy of thrombolysis in patients with pulmonary thromboembolism. 27,28 Therefore, the Paco 2 -Petco 2 gradient can be used to evaluate or monitor progression of various pulmonary or cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, relative inaccuracy is seen in conditions of ventilationperfusion mismatch. 18,19 Transcutaneous CO 2 monitoring is a noninvasive technique for measuring CO 2 levels. However, transcutaneous CO 2 monitoring is not tolerated in very low birth weight infants because of their fragile skin, and the technique is affected by acidosis and hypoxia.…”
mentioning
confidence: 99%